A study on the functional and radiological outcome with complications in the management of proximal humerus fractures operated with proximal humerus internal locking osteosynthesis system - Banerjee, Manideep; Biswas, Rajeev; Roy, Archak (International Journal of Research in Orthopaedics, 2023)
Background: A number of opinions exist regarding the management of proximal humerus fractures starting from conservative to tension band-wiring to internal fixation with plates. The aim of this study is to assess the functional outcome, the radiological outcome and the complications associated with the management of proximal humerus fractures treated with proximal humerus interlocking osteosynthesis system (PHILOS). Methods: A prospective descriptive study was undertaken comprising of 40 patients. Closed proximal humerus fractures meeting Neer’s criteria for operative displacement were enrolled. Patients underwent open reduction internal fixation with PHILOS plate. Post-operative radiological outcome was estimated with follow-up x-rays, functional outcome using the Constant and Murley score. Results: 60% patients were female, with the most common mode of injury being fall at a ground level. Late complications were noted in 25% of patients, which were malunion 5%, joint stiffness 10%, joint instability 5% and heterotopic ossification 5%. The mean Constant and Murley score was 79.5 and it was found to be statistically significant to the type of fracture according to the Neer’s classification (Kruskal Wallis test, p=0.005). Joint stiffness was also found to be statistically significantly correlated to the type of fracture pattern (Chi square test, p=0.016). The average time to union was 10 weeks. Conclusions: Thus, by this study it can be expressed due to appropriate articular reduction by open reduction and by the use of a fixed angle implant like the PHILOS plate, operative management of proximal humerus fractures by the said implant is a viable option to enable quick and early rehabilitation of patients.